Evaluation of the clinical impact of bone marrow cultures in current medical practice - Gal Sharvit; Daniel Schwartz; Gabriel Heering; Alexander Shulman; Abraham Avigdor; Galia Rahav; Amos Toren; Arnon Nagler; Jonathan Canaani (Scientific Reports, 2022)
Abstract The clinical yield and benefit of performing bone marrow cultures for various clinical indications has been challenged and their clinical necessity remains debatable. We sought to assess the clinical yield and benefit of performing routine bone marrow cultures and determine whether various clinical, laboratory, and imaging parameters were predictive of a diagnostic bone marrow culture. This was a single center retrospective analysis of all patients who underwent a bone marrow study comprising bone marrow cultures from January 1, 2012, through March 1, 2018. Baseline clinical data were extracted from the institution's electronic medical records system. The analyzed cohort consisted of 139 patients with a median age of 46 years (range 4 months to 85 years). The most common indication for a bone marrow study was workup of a fever of unknown origin (105 patients, 76%) while investigation for infection in immunocompromised patients accounted for 22 cases (16%) and suspected tuberculosis was the reason for acquisition of bone marrow cultures in 6 patients (4%). Only 3 patients had positive bone marrow cultures, yielding in 2 patients a diagnosis of Mycobacterium avium and in one patient a microbiologically unclassifiable fungal infection. A univariate analysis revealed that mean age, hemoglobin level, platelet count, c-reactive protein levels, gender, indication for bone marrow study, yield of blood cultures, and contribution of imaging studies and bone marrow pathology results were not significantly different between patients with diagnostic and non-diagnostic bone marrow cultures. Mean white blood cell count was found to be significantly lower in patients with diagnostic bone marrow cultures (2.4 × 103/µL versus 8.7 × 103/µL; P = 0.038). We conclude that for most patients, performance of bone marrow cultures holds limited clinical value.